Uretero-ureteral anastomosis: An alternative for patients with duplicated collecting system associated diseases (2015)
Introduction and objectives: Duplicated collecting system is a common congenital renal disorder and has an incidence of 0.8%. There are several treatment options available for the severely dilated ureter or reflux associated with a duplicated system, including hemi-nephrectomy, uretero-ureteral anastomosis, and ureteroneocystostomy. The aim of this article is to present our experience of the uretero-ureteral anastomosis as an alternative for patients with renal pathology associated with duplicated collecting system. Materials and methods: A retrospective review was performed, between July 2011 and April 2014, on the medical records of patients with duplicated collecting system and associated disorders and who underwent uretero-ureteral anastomosis. Demographics, such as age, sex, laterality and postoperative outcomes were analysed. Results: A total of 10 patients underwent uretero-ureteral anastomosis, of whom 7 were female and 3 were male. The mean age of patients was 5 years (1-13 years). There were 6 patients with right pathology; 9 patients had urinary tract infection, and one had permanent urinary incontinence. Ectopic ureter was diagnosed in 4 patients, 3 patients had intravesical ureterocele and 3 had vesicoureteral reflux to the lower system. Seven upper to the lower anastomosis system and 3 lower to the upper system anastomosis were performed. All were made by 2 cm inguinal incision, and all patients had a double J catheter bypass. Conclusions: The uretero-ureteral anastomosis is a reliable and safe alternative with low morbidity. It is effective for the treatment of patients with duplicated collecting system associated to renal pathology. © 2015 Sociedad Colombiana de Urología.